Hakikat dan Tujuan Pendidikan Islam - Habiebah, Najwa; Albina, Meyniar (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this paper is to find out what Islamic education really is and what its essence is. This study is a literature study. The results show that the purpose of Islamic education is to form individuals who believe, fear Allah Swt, and have noble character in a balanced manner. In Islamic education, the task of an educator is to educate and teach according to his knowledge. Overall, the person responsible for teaching is the educator. In essence, the task of Islamic education is to guide students from stage to stage of their lives until they reach the optimal point. Basically, the purpose of Islamic education itself is essentially identical to the purpose of Muslim or human life. Where, the purpose of human life is as a servant of Allah and also the Caliph. Meanwhile, the purpose of Islamic education is to achieve a balance of the growth of the human personality (students) as a whole and balanced which is done through soul training, rational human intellectual self, feelings and senses. It can be concluded that overall education in Islamic philosophy education lies in the realization of perfect submission to Allah both personally, community and all mankind.